2020
DOI: 10.3233/wor-203100
|View full text |Cite
|
Sign up to set email alerts
|

Maximum handgrip strength as a function of type of work and hand-forearm dimensions

Abstract: BACKGROUND: Handgrip strength is a measurement of upper extremity functionality and an indicator of overall physical ability. OBJECTIVES:The objective of this study was to compare maximum handgrip strength (MGS) between manual workers and office employees and to investigate if the expected difference is related to the anthropometric dimensions of the workers' hands and forearms. METHODS: This was a cross-sectional study with a sample of 1740 male workers (905 light manual workers; and 835 office employees), ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 38 publications
0
17
1
Order By: Relevance
“…Their results were similar to males (48.2 vs. 48.1 kg) and females (30.2 vs. 31.5 kg) of our study for the same age category. In this study, the results showed lower values respect to those reported by Rostamzadeh et al [63], which compared maximum handgrip strength between light manual workers and office employees, and found approximately 12.4% of the difference between groups (59 kg and 51.9 kg, respectively). Both female and male groups showed lower handgrip values than those previously reported by Perroni et al [4] for novice and volunteer firefighter recruits (49.8 kg and 50.1 kg, respectively).…”
Section: Plos Onecontrasting
confidence: 91%
“…Their results were similar to males (48.2 vs. 48.1 kg) and females (30.2 vs. 31.5 kg) of our study for the same age category. In this study, the results showed lower values respect to those reported by Rostamzadeh et al [63], which compared maximum handgrip strength between light manual workers and office employees, and found approximately 12.4% of the difference between groups (59 kg and 51.9 kg, respectively). Both female and male groups showed lower handgrip values than those previously reported by Perroni et al [4] for novice and volunteer firefighter recruits (49.8 kg and 50.1 kg, respectively).…”
Section: Plos Onecontrasting
confidence: 91%
“…Some studies have also shown that although height and weight are positively correlated with hand strengths in pubertal years, the influence of these variables is considerably smaller than that of either gender or age [17,21]. Considering anthropometric dimensions, previous studies have found a strong correlation with handgrip and pinch strengths in adults [22][23][24], which was confirmed in children and adolescents in few studies [25]. In addition, there are contradictory findings in the studies on the anthropometric variables affecting hand strengths (HGS and PSs) in different age ranges [20,26].…”
Section: Introductionmentioning
confidence: 99%
“…HGS is influenced by many factors, such as age, gender, height, weight, hand dominance, occupation, physical activity level and geographical areas [ 4 , 6 ]. Previous studies have found that HGS has a nonlinear relationship with age, usually peaking during the 4 th decade of life and then declining gradually [ 6 ]. HGS also increases linearly with height and weight and is notably higher in the dominant hand [ 4 , 6 ].…”
Section: Introductionmentioning
confidence: 99%